Risk factors for cardiovascular diseases and geriatric syndromes – epidemiology issues and relationship in older age patients - N. E. Titova; N. V. Semionenkova; S. M. Bazhenov; D. S. Bazhenova; E. D. Golovanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The frequency of occurrence of geriatric syndromes (senile asthenia, depression, cognitive disorders) investigated in relation to some factors of cardiovascular risk (arterial hypertension, obesity) in patients of older age groups – residents of the city (1st sample) and rural (2nd sample) of Smolensk region. A comprehensive geriatric assessment of 480 patients over 65 years old was carried out with the analysis of case histories and outpatient records. The scale for screening senile asthenia (“Age is not a hindrance”), MMSE scale, GDS-15 was used. The analysis of the obtained results showed that the frequency of occurrence of senile asthenia among the residents of the village was lower than among the residents of the city (p <0.05). In both samples, the incidence of depression was twice as high in patients with senile asthenia and was associated with the female sex. At the age of 65–74, the >incidence of depression among rural residents was comparable to urban residents (31% and 29.7%, respectively, p ˃ 0.05), but among people over 75 years of age, its prevalence was lower among rural residents (35, 5% versus 52.3%, respectively, p < 0.05). A decline in cognitive status in patients under 75 years of age is associated with high blood pressure, while in those over 75 years of age, this relationship was inverse. The prevalence of obesity was higher in patients without senile asthenia.